PEMANFAATAN MEDIA VIDEO PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS X BAHASA 1 DI SMA NEGERI 2 MALANG - Athifa Khairunnisa; Muhammad Sulistiono; Lia Nur Atiqoh Bela Dina (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
The use of instructional media increases the likelihood that students will develop the attitudes and skills they need. In addition to showing teaching materials, video media also helps teachers to convey messages or materials during the learning process, that is, to change the way they teach. content-based instruction. The planning of video media in learning, the implementation process and the results of the application of video media in learning PAI in class X Bahasa 1 SMA Negeri 2 Malang provides basic information on the use of media Of video. Because this research is a type of descriptive research, the authors use qualitative research with the type of case study in this study. Observations, interviews, and desk studies were used to obtain data. Based on the research findings on the use of video media in PAI subjects in the X Bahasa 1 SMA Negeri 2 Malang class, the teacher first identified the needs and characteristics before planning through video media. create goals for students, create resources, collect video content and review. Teacher-generated lesson plans are followed through the implementation phase, which makes use of video material. Daily assignments that involve asking students questions to measure student achievement through video media are used to collect results from the video media application itself.Keyword: Use of video media, Islamic religious education